A Study on Japan’s Dance Teaching in the Junior Period as Seen from the Narratives of Dance Instructors - SOMIYA, Yuko; TERAYAMA, Yumi (Research Journal of JAPEW, 2022)
In this study, we aim to reveal what sort of instruction dance instructors in the “junior period” of Japan provides and their respective intention. As for the survey method, interview surveys were conducted with five dance instructors.From the narratives of five dance instructors with good reputation for providing instruction students under the age of 18, we came to witness that the teachers are highly conscious of the so-called “fundamental instruction”. It’s suggested that we aim for to attain body（the dancing body）, expression（the expressing body）, and thinking（motions） as the base for continuous activities in the future（18-year-old and over）, the foundation of dancing. The formation of a danceable body was, in fact, similar even over the age of 18.In this survey, it can be considered that the basic body and thoughts are formed during the junior period with a view to activities for people over the age of 18.